The renewed helicopter fleet is the key factor in the social and economic development of the regions - Yu. V. Krivolutsky; E. Yu. Krivolutsky (Путеводитель предпринимателя)
Helicopters are the main transport in the North, Siberia, and Far East regions. The social and economic development of the regions is mostly defined by the condition and development of the helicopters’ fleet. Also, it is defined by the density and productiveness of the work of helicopter aviation companies with the customers. The ability of aviation companies to buy new types of helicopters on the one hand, and the ability of current and potential customers to order transportation services on the other hand, will define the scope and the speed of development of production and social domain of the regions.